Perception, trends and impacts of climate change in Kailali District, Far West Nepal - Thapa, Lal Bahadur; Thapa, Himanchal; Magar, Bimala Gharti (International Journal of Environment, 2015)
Correction: On 31/12/2015 the author’s name Binala Gharti Magar was changed to Bimala Gharti Magar Perception and place-based studies give useful information on climate change in context of Nepal due to having its wide geographical, climatic, biological and cultural diversity. A household survey and focus group discussions were carried out in this study to document local people’s perceptions on climate change in Kailali district of Nepal. Most of respondents in the study area have perceived that temperature and fog are increased; and rainfall and hail are decreased with severe fluctuation. Trend of temperature supports local people’s perception. People have noticed impacts of these changes in vegetation, plant phenology and agriculture. Fundamentally, they have observed that certain plant species are decreasing, increasing and showing changes in flowering and fruiting time. This information could have significance for future research to identify climate change sensitive or indicator plants. International Journal of Environment Vol.4(4) 2015: 62-76